Cost–effectiveness of pharmacogenetics in anticoagulation: international differences in healthcare systems and costs. (September 2012) - Verhoef, Talitha I; Redekop, William K; van Schie, Rianne MF; Bayat, Samira; Daly, Ann K; Geitona, Mary; Haschke-Becher, Elisabeth; Hughes, Dyfrig A; Kamali, Farhad; Levin, Lars-Åke; Manolopoulos, Vangelis G; Pirmohamed, Munir; et al.
Genotyping patients for CYP2C9 and VKORC1 polymorphisms can improve the accuracy of dosing during the initiation of anticoagulation with vitamin K antagonists (coumarin derivatives). The anticipated degree of improvement in the safety of anticoagulation with coumarins through genotyping may vary depending on the quality of patient care, which varies both with and among countries. The management and the cost of anticoagulant care can therefore influence the cost–effectiveness of genotyping within any given country. In this article, we provide an overview of the cost–effectiveness of pharmacogenetics-guided dosing of coumarin derivatives. We describe the organization of anticoagulant care in the UK, Sweden, The Netherlands, Greece, Germany and Austria, where a genotype-guided dosing algorithm is currently being investigated as part of the EU-PACT trial. We also explore the costs of anticoagulant care for the treatment of atrial fibrillation in these countries.